2013
DOI: 10.1371/journal.pone.0070674
|View full text |Cite
|
Sign up to set email alerts
|

Noise Exposure and Hearing Impairment among Chinese Restaurant Workers and Entertainment Employees in Hong Kong

Abstract: BackgroundNoise-induced hearing loss (NIHL) is a major concern in the non-manufacturing industries. This study aimed to investigate the occupational noise exposure and the NIHL among Chinese restaurant workers and entertainment employees working in the service industry in Hong Kong.MethodsThis cross-sectional survey involved a total of 1,670 participants. Among them, 937 were randomly selected from the workers of Chinese restaurants and 733 were selected from workers in three entertainment sectors: radio and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 26 publications
1
21
1
4
Order By: Relevance
“…Presbycusis is usually seen after the age of 60 and may show a different pattern on audiogram, leading to a down sloping curve without a notch on audiogram. Also, distinction of presbycusis from noise-induced hearing loss may be difficult in the setting of combined occupational noise exposure and older age (18). Although the results showed that increasing of age increases the hearing loss, to better assess we need for screening and assessment of various factors including the underlying factors.…”
Section: Discussionmentioning
confidence: 97%
“…Presbycusis is usually seen after the age of 60 and may show a different pattern on audiogram, leading to a down sloping curve without a notch on audiogram. Also, distinction of presbycusis from noise-induced hearing loss may be difficult in the setting of combined occupational noise exposure and older age (18). Although the results showed that increasing of age increases the hearing loss, to better assess we need for screening and assessment of various factors including the underlying factors.…”
Section: Discussionmentioning
confidence: 97%
“…Viu-se, conforme se esperava, a associação, com gradiente positivo, entre o desfecho e a idade 9,16,19 . A significância estatística com a antiguidade no cargo ocupado nas faixas de 5-10 anos e a idade entre 20 e 47 anos não foi surpreendente 24 .…”
Section: Discussionunclassified
“…Sexo masculino, faixa etária menos jovem, antiguidade no cargo e consumo diário de álco-ol foram associados à perda auditiva de origem ocupacional na amostra de 1.670 trabalhadores do setor de entretenimento e restaurante 19 . A relação entre o aumento da perda auditiva de acordo com a idade e o tempo de serviço também foi confirmada em outros estudos 16,20 .…”
Section: Discussionunclassified
“…(69,12) These studies concluded that environmental sound levels in restaurants can exceed 85 dBA during operating hours. (6,9) In a case study of 30 restaurants in Florida, Rusnock and Bush (7) found average restaurant sound levels ranged from 58 to 97 dBA.…”
Section: Introductionmentioning
confidence: 99%
“…Lao et al (12) performed a cross-sectional survey of hearing loss in non-manufacturing industries, which included personal noise assessment of 22 restaurant workers in Hong Kong. This work identified mean personal daily exposure among cooks (n = 20) was 92.9 dBA and among dishwashers (n = 2) 90.5 dBA, reporting that three personal exposures exceeded 100 dBA.…”
Section: Introductionmentioning
confidence: 99%